Street Teaching in the Tenderloin : Jumpin' Down the Rabbit Hole - Stannard-Friel, Don (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book is an ethnographic account of San Francisco's most inner city neighborhood, the Tenderloin. Using its streets as campus and its people as teachers, Stannard-Friel uses storytelling as a way of explaining why inner city social problems, such as homelessness, drugs, prostitution, untreated mental illness, and death of young people by murders and suicides, exist and persist there. The work delves into who lives in the Tenderloin and why, the role of dedicated service providers in meeting people's needs and encouraging social change, and what lessons university students, many coming from their own challenging backgrounds, learn through community engagement and service learning that encourage understanding, compassion, and meaningful contributions to society. The work also explores how life in the area is changing, and why so many youth report that they "love living in the Tenderloin." .
Keywords: Social sciences.; Social structure.; Social inequality.; Sociology, Urban.; elektronické knihy; electronic books